The recently identified flavivirus Bamaga virus is transmitted horizontally by Culex mosquitoes and interferes with West Nile virus replication in vitro and transmission in vivo. - Agathe M G Colmant; Sonja Hall-Mendelin; Scott A Ritchie; Helle Bielefeldt-Ohmann; Jessica J Harrison; Natalee D Newton; Caitlin A O'Brien; Chris Cazier; Cheryl A Johansen; Jody Hobson-Peters; Roy A Hall; Andrew F van den Hurk (Public Library of Science (PLoS), 2018)
Arthropod-borne flaviviruses such as yellow fever (YFV), Zika and dengue viruses continue to cause significant human disease globally. These viruses are transmitted by mosquitoes when a female imbibes an infected blood-meal from a viremic vertebrate host and expectorates the virus into a subsequent host. Bamaga virus (BgV) is a flavivirus recently discovered in Culex sitiens subgroup mosquitoes collected from Cape York Peninsula, Australia. This virus phylogenetically clusters with the YFV group, but is potentially restricted in most vertebrates. However, high levels of replication in an opossum cell line (OK) indicate a potential association with marsupials. To ascertain whether BgV could be horizontally transmitted by mosquitoes, the vector competence of two members of the Cx. sitiens subgroup, Cx. annulirostris and Cx. sitiens, for BgV was investigated. Eleven to thirteen days after imbibing an infectious blood-meal, infection rates were 11.3% and 18.8% for Cx. annulirostris and Cx. sitiens, respectively. Cx. annulirostris transmitted the virus at low levels (5.6% had BgV-positive saliva overall); Cx. sitiens did not transmit the virus. When mosquitoes were injected intrathoracially with BgV, the infection and transmission rates were 100% and 82%, respectively, for both species. These results provided evidence for the first time that BgV can be transmitted horizontally by Cx. annulirostris, the primary vector of pathogenic zoonotic flaviviruses in Australia. We also assessed whether BgV could interfere with replication in vitro, and infection and transmission in vivo of super-infecting pathogenic Culex-associated flaviviruses. BgV significantly reduced growth of Murray Valley encephalitis and West Nile (WNV) viruses in vitro. While prior infection with BgV by injection did not inhibit WNV super-infection of Cx. annulirostris, significantly fewer BgV-infected mosquitoes could transmit WNV than mock-injected mosquitoes. Overall, these data contribute to our understanding of flavivirus ecology, modes of transmission by Australian mosquitoes and mechanisms for super-infection interference.